Estrutura da rede de interações abelhas-flores no Pantanal da Serra do Amolar - NATHALIA SOUZA ROCHA (2021)
The analysis of interaction networks is an important tool in studies in community ecology, helping to reveal their organization and the functioning of complex systems of interacting species and how they can respond to ongoing environmental changes. The interactions between bees and plants are essential for the reproduction of most native angiosperms (87.5%) in Brazil, and growing evidence suggests that many pollinator populations, including bees, are experiencing decline worldwide. The objective of this work was to evaluate the structure of the bee-plant interactions network in the Serra do Amolar region, Mato Grosso do Sul, evaluating the frequency and behavior of bees visiting the flowers, as well as the morphological characteristics of these two groups, through a bimonthly sampling over a year. There were 37 species of bees visiting 86 species of plants, totaling 123 species composing the network of interactions. The network presented low connectivity, was significantly nested and showed moderate specialization. The interactions were influenced by the habit of plants and corolla types of visited flowers. The eusociality of the bees was a determinant characteristic for the patterns of the network, being an evidence of the persistence of these species in the habitat. The study also showed that the exotic bee, Apis mellifera, is the main connector of modules within the network. The Serra do Amolar region consists, primarily, of areas of vegetation of Deciduous Seasonal Forest, Wooded Savanna and Woody Grassy Savanna therefore, further studies including these other types of environments should be carried out, since they are important to understand the functioning of the overall ecosystem and the interactions that occur in the area.